2014
DOI: 10.3390/ijms151119516
|View full text |Cite
|
Sign up to set email alerts
|

X-ray-Induced Changes in the Expression of Inflammation-Related Genes in Human Peripheral Blood

Abstract: Using quantitative real-time polymerase chain reaction (PCR) array, we explored and compared the expression changes of inflammation-related genes in human peripheral blood irradiated with 0.5, 3, and 10 Gy doses of X-rays 24 h after exposure. Results indicated that the expression of 62 out of 84 genes was significantly altered after X-ray radiation. Among these 62 genes, 35 (such as TNFSF4) are known to be associated with radiation response, but others are novel. At a low radiation dose (0.5 Gy), 9 genes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…64 On the contrary, some reports indicate no change in RBCs and Hb levels due to gamma-ray exposure in mice. 65,66 In the present study, RBC count and Hb levels remained unaltered after X-ray exposure, which might be due to the remarkable regenerative capacity of blood cells to recover in short periods of time. 67 In the present study, elevation in WBC counts was observed in X-ray exposed mice when compared to control counterparts.…”
Section: Discussionmentioning
confidence: 41%
“…64 On the contrary, some reports indicate no change in RBCs and Hb levels due to gamma-ray exposure in mice. 65,66 In the present study, RBC count and Hb levels remained unaltered after X-ray exposure, which might be due to the remarkable regenerative capacity of blood cells to recover in short periods of time. 67 In the present study, elevation in WBC counts was observed in X-ray exposed mice when compared to control counterparts.…”
Section: Discussionmentioning
confidence: 41%
“…As a highly sensitive and reliable method of gene expression profiling, qPCR array combines qRT-PCR and gene chips which can screen differentially expressed genes based on mRNA. qPCR array is a useful tool for studies on signaling pathway [ 27 , 28 ]. In agreement with these findings, in the current study, the results demonstrated that 44 genes (including MyD88-dependent and nondependent TLR4, NLRS, MARK, and NF- κ B) were upregulated after LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The IRF input into macrophage polarization upon radiotherapy remains poorly investigated. In fact, according to the authors’ knowledge, alterations in IRF1, 2, 3, and 5 activity were reported in irradiated macrophages so far [ 72 , 73 , 202 ]. Low dose-irradiation induces ROS generation with subsequent ATM activation to stimulate IRF5 expression and M1-like macrophage polarization with increased IL-6, TNF-α, and IFN-γ [ 145 ].…”
Section: Macrophage Transcriptional Reprogramming During Chemo- Anmentioning
confidence: 99%
“…High radiation doses reduce IRF2 and 5 levels increasing numbers of M2-like macrophages in the tumor [ 151 ]. At least for the high-dose irradiation IRF1 is suppressed in monocytes, while upregulated in macrophages, suggesting the different responses from infiltrated cells and TAMs [ 72 , 73 ].…”
Section: Macrophage Transcriptional Reprogramming During Chemo- Anmentioning
confidence: 99%